Enshrined white marble image of Rishabhnatha - Temples of India Project Team (Jio Institute, 2024)
The enshrined white marble image, is probably of Rishabhnatha in the garbhagriha (sanctum sanctorum) of the Adinatha Temple. The Tirthankara, with a crown and elongated earlobes, is seated in padmasana (lotus pose) on a lotus pedestal. The base of the sculpture has an inscription incised with red colour.